The Implementation of the Republic of Indonesian Supreme Court Regulation Number 3 of 2022 Concerning Electronic Mediation in Court: A Case Study - Maria Rosalina; Az Zahra Zulfikar (Qubahan Academic Journal)
The current development and progress of communication and information technology has prompted the Lubuk Pakam District Court to change the mediation implementation system which was originally carried out manually to electronic mediation as regulated in Perma Number 3 of 2022.In the implementation of this electronic mediation, problems are still found, due to obstacles from inside or outside the court. This is what drives researchers to conduct research. Formulation of the problem of how to implement Perma and what are the obstacles and how to overcome obstacles in implementing this Perma. The purpose of this research is to find out the implementation of Perma and find out the obstacles and how to overcome these obstacles. The methodology in this study uses an empirical juridical approach where research is carried out directly through interviews with research objects in the field, then connected with secondary data. Results and discussion, Perma has been implemented at the Lubuk Pakam District Court, but not yet fully because there are obstacles such as online mediation carried out by agreement of the parties, there are no internet-based mediation facilities, the internet network is unstable, judge mobility high etc. Conclusion Perma has been implemented at the Lubuk Pakam District Court, but it has not been maximized, due to several obstacles.